Occurrence and risk assessment of organochlorine pesticide residues in tea and herbal products in Spain - Diez, Raquel; Lopez, Cristina; Rodriguez, Jose M.; de la Puente, Raul; Romero, Beatriz; Vazquez, E. Milena; Diez, M. Jose; Fernandez, Nelida; Sahagun, Ana M. (Frontiers in Sustainable Food Systems, 2025)
Organochlorine pesticides (OCP) are persistent pollutants well known for their ability to bioaccumulate. So, food contamination with these compounds is of concern for human health. The levels of nine OCP were determined in 60 samples of black tea and two herbal products (chamomile and linden) commercially available in Spain. The analysis was carried out by gas chromatography coupled with electron capture detector (GC-ECD), and confirmed by gas chromatography-mass spectrometry (GC-MS). The linearity, accuracy, precision, and limits of quantification and detection of the method were validated. OCP residues were detected in 66.7% of the samples at low levels, being always below the European maximum residue limits (MRL). No OCP was found in black tea samples, and only four pesticides were present in linden and chamomile products: 2,4′-DDD was the most frequently OCP detected, followed by aldrin, endrin, and 4,4′-DDD. The health risk assessment indicated that the presence of OCP in black tea and the two herbal products does not pose any risk to consumers.